Effects of cognitive training program on cognitive abilities in stroke patients - Khanthee, Rakreuthai; Panyamee Dhippayom, Jananya; Munkhetvit, Peeraya (Journal of Associated Medical Sciences, 2016)
Background: Impairment of cognitive functions has an impact on an ability to pursue daily life occupations in stroke patients. As a consequence, cognitive training program for enhancing cognitive functions in this patient group is needed. Objectives: To examine the effect of cognitive training program on 4 skills of cognitive functions including orientation, attention, memory, and executive functions, in stroke patients Materials and methods: Participants were 10 cognitive impaired stroke patients as screened by the Mini-Mental State Examination: Thai Version (MMSE-Thai-2002). They were purposively recruited and received the cognitive training program 3 times a week for 6 consecutive weeks. The outcome measures for assessing cognitive abilities were the Trail Making Test, Thai Cognitive-Perceptual Test (Thai-CPT), and Dynamic Lowenstein Occupational Therapy Cognitive Assessment for Adults (DLOTCA). Data was analyzed using descriptive statistics and Wilcoxon Signed Ranks Test. Results: After receiving the cognitive training program, participants had significant improvement in 4 cognitive skills; orientation, attention, memory, and executive functions (α=0.05). Conclusion: Cognitive training program of this study could enhance cognitive abilities in stroke patients. Bull Chiang Mai Assoc Med Sci 2016; 49(2): 298-306. Doi: 10.14456/jams.2016.39